Seismic vulnerability procedures for historical masonry structural aggregates: Analysis of the historical centre of Castelpoto (South Italy). (February 2023) - Chieffo, Nicola; Formisano, Antonio; Lourenço, Paulo B.
Abstract: In historical centres, it is very difficult to analyse masonry buildings as independent structures since they have common wall panels with adjacent structural units. These types of building compounds interact with each other under seismic actions, so their behaviour differs from that of individual buildings considered isolated structures. In this framework, multilevel procedures for assessing the vulnerability of masonry building aggregates are examined in the paper and illustrated in detail through the application of a case study in Castelpoto, a municipality of Benevento (Italy). From one side, an index-based evaluation methodology is proposed, appropriately calibrated on the results of the analysis of macroelements on a significant number of grouped buildings, also considering the interactions among adjacent buildings. On the other side, a method based on mechanical analysis is applied at the building scale to evaluate, more realistically, the seismic behaviour of clustered structural units through suitable capacity and fragility assessments.